Sustainability labels as heuristic cues for clothing consumption - Wallin, Måns Erik Henry (2021)
This thesis strives to understand if usage of sustainability labels (Fair-trade labels) acts as heuristic cues for consumers when they are purchasing clothes, and if the sustainability labels also make people infer other things about the piece of clothing based on the sustainability label. This thesis explores the hypotheses by conducting an experiment (survey) with t-shirts as the material, that is manipulated between two conditions, high and low involvement, to see if participants, when processing the information about the t-shirts, are more inclined to use the label as a cue to make a decision, and if the participants are more likely to use the label in the low or high involvement condition. The t-shirts also come with either a positive or negative product description that portrayed the t-shirts sustainable/non-sustainable aspects. 106 evaluations are collected between the two conditions, and then analysed based on dual-process theories. The result from the study shows that t-shirts with sustainability labels are always preferred over t-shirts without labels, and labels are used by participants to make other inferences about the t-shirts: t-shirts with labels are perceived as superior over t-shirts without label, and that involvement only affected participants when there was no label present. The t-shirts with a positive product description are always ranked higher than those with a negative product description.